2022
DOI: 10.3390/metabo12050457
|View full text |Cite
|
Sign up to set email alerts
|

Oral Adelmidrol Administration Up-Regulates Palmitoylethanolamide Production in Mice Colon and Duodenum through a PPAR-γ Independent Action

Abstract: Adelmidrol is a promising palmitoylethanolamide (PEA) analog which displayed up-and-coming anti-inflammatory properties in several inflammatory conditions. Recent studies demonstrated that Adelmidrol is an in vitro enhancer of PEA endogenous production, through the so called “entourage” effect. The present study investigated the ability of Adelmidrol (1 and 10 mg/Kg per os) to increase the endogenous level of PEA in the duodenum and colon of mice after 21-day oral administration in the presence and absence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The following chemical variations also support the increase in B. cinerea membrane rigidity: i) the significant reduction in monoolein, an unsaturated lipid that significantly increases the fluidity of the lipid bilayer 46 , and ii) a reduction in the ergosterol byproduct ergocalciferol, which is described to increase membrane fluidity 47 . We also observed a reduction in palmitamide, an endogenous fatty acid synthesized from phosphatidylethanolamine at the plasma membrane 48 , and described it as a lipid messenger involved in cyclooxygenase activation for ROS detoxification 49 . A similar response in C. elegans was reproduced upon treatment with cyclo(Pro-Tyr), which elicited plasma membrane remodeling and enhanced the detoxification of ROS [50][51][52] .…”
Section: Discussionmentioning
confidence: 85%
“…The following chemical variations also support the increase in B. cinerea membrane rigidity: i) the significant reduction in monoolein, an unsaturated lipid that significantly increases the fluidity of the lipid bilayer 46 , and ii) a reduction in the ergosterol byproduct ergocalciferol, which is described to increase membrane fluidity 47 . We also observed a reduction in palmitamide, an endogenous fatty acid synthesized from phosphatidylethanolamine at the plasma membrane 48 , and described it as a lipid messenger involved in cyclooxygenase activation for ROS detoxification 49 . A similar response in C. elegans was reproduced upon treatment with cyclo(Pro-Tyr), which elicited plasma membrane remodeling and enhanced the detoxification of ROS [50][51][52] .…”
Section: Discussionmentioning
confidence: 85%
“…Accordingly, the exogenous administration of PEA to effectively ‘top up’ the body’s own supply is regarded as a promising approach [ 54 ]. Interestingly, other ALIAmides, such as Adelmidrol and PGA, have recently been found to increase the endogenous levels of PEA [ 55 , 56 , 57 ].…”
Section: Mimicking and Supporting The Healing Power Of Naturementioning
confidence: 99%
“…Besides increasing PEA levels, as previously mentioned, these fatty acid amides are suggested to interact with different receptors. PGA, for example, is considered to exert its protective function through a toll-like receptor 4 antagonism [ 94 ], while the precise molecular targets of Adelmidrol are still debated [ 55 , 95 ].…”
Section: A Brief Insight Into Pea Metabolism and Molecular Targetsmentioning
confidence: 99%
“…Adelmidrol is a synthetic derivate of azelaic acid which works as a palmitoylethanolamide (PEA) enhancer increasing endogenous PEA levels [ 59 ]. Recently, it has been demonstrated that Adelmidrol is able to significantly increase the endogenous PEA level in the duodenum and colon of healthy mice in a dose/time-dependent and PPAR-γ-independent manner [ 60 ]. As with PEA, Adelmidrol belongs to the family of Autacoid Local Injury Antagonist Amides (ALIAmides) and its amphiphilic and amphipathic characteristics make Adelmidrol particularly soluble and suitable for topical [ 61 , 62 ] and intra-articular administration.…”
Section: Intra-articular Adelmidrol: a New Therapeutic Option For Oamentioning
confidence: 99%